Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Creativity and Cognition 2022
DOI: 10.1145/3527927.3532813
|View full text |Cite
|
Sign up to set email alerts
|

How Researchers Manage Ideas

Abstract: Research ideas are pivotal in research practice. While research domains, topics, and methods are often outlined by specific research fields, the process of capturing and developing research ideas is less categorical. Conceiving and developing research ideas requires continuous creative thinking, usually supported by various different tools, each more or less carefully selected by a researcher to fulfill a specific purpose. In this paper, we investigate the creative work practices of academic researchers, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The higher assessment score of the experimental groups showed that the use of organized training with the integration of Zettelkasten that enabled the students to draw links between the information and knowledge resulted in an enhanced learning experience, contributing to better understanding. This finding of the study is found to be in line with the assertions of Ratcliffe (2021) [5]; the use of Zettelkasten can enhance the students' learning and training outcomes due to their ability to internalize information and establish a better conceptual understanding rather than cramming the knowledge.…”
Section: -Discussion Of the Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…The higher assessment score of the experimental groups showed that the use of organized training with the integration of Zettelkasten that enabled the students to draw links between the information and knowledge resulted in an enhanced learning experience, contributing to better understanding. This finding of the study is found to be in line with the assertions of Ratcliffe (2021) [5]; the use of Zettelkasten can enhance the students' learning and training outcomes due to their ability to internalize information and establish a better conceptual understanding rather than cramming the knowledge.…”
Section: -Discussion Of the Findingssupporting
confidence: 88%
“…Zettelkasten is a technique that was used by a German scholar, Niklas Luhman, which is also known as Slip Box [4]. Studies have shown that this German scholar was highly productive as he used the Zettelkasten technique for learning and development [4,5]. Luhmann gave several distinct explanations of his Zettelkasten.…”
Section: -1-zettelkasten Techniquementioning
confidence: 99%